FAKTOR YANG BERHUBUNGAN DENGAN DERMATITIS KONTAK AKIBAT KERJA PADA PEKERJA PROYEK BANDARA - Harumi Kusuma Wardani; Mashoedojo Mashoedojo; Nurfitri Bustamam (Universitas Airlangga, 2018)
The incidence of contact dermatitis in Indonesia varies greatly and affects most workers. Epidemiological studied showed the incidence of Occupational Contact Dermatitis (OCD) was 0.5–1.9 cases/1000 workers/year. Aircarft Filling Depot Project at Juanda Airport is a construction project that is working on hydrant system and topping up development. This study was aimed at identifying risk factors of OCD among the project workers. A cross sectional design was used on 47 workers whom randomly selected during period May-June 2017. Data was collected using a questionnaire with the researcher’s guide. Occupational Contact Dermatitis is diagnosed by general practitioner that located in Naval Hospital (RUMKITAL) dr. Soekantyo Jahja Surabaya. Occupational contact dermatitis risk factors were analyzed using Chi-square test, followed by multiple logistic regression test. Of 47 workers, 21 (43.8%) experienced OCD. The use of personal protective equipment (PPE), duration of contact, personal hygiene, and history of skin diseases were associated with OCD (p < 0.01), whereas the type of work was not related to OCD (p = 0.491). The most dominant factor causing OCD was personal hygiene (OR = 9.659), followed by duration of contact (OR = 8.576), and history of skin disease (OR = 3.420). In conclusion, factors of use of PPE, length of contact, personal hygiene, and history of skin relationship with DKAK, while the type of work is not related to DKAKKeywords: aircraft filling depots project, occupational contact dermatitis, risk factor